The analysis of existing and perspective methods of indemnification of jet capacity - Хіргій, А. Г.; Москаленко, О. В. (Problems of Informatization and Control, 2005)
In clause is stated problems connected with to a low degree of quality of the electric power on a railway transportation, mathematical models for account of jet capacity and methods of indemnification it with the help of static and dynamic condenser installations